Half-blown rose : a novel - Cross-Smith, Leesa, 1978- (Grand Central Publishing, 2022)
"Having grown up the privileged daughter of artists, Vincent has a life that is lovely in many ways. At forty-four, she enjoys strolling the streets of Paris and teaching at the modern art museum; she has a vibrant group of friends; and she's even caught the eye of a young, charismatic man named Loup. But Vincent is also in Paris to escape a painful betrayal: her Irish husband, Cillian, has published a bestselling book divulging secrets about his past and their marriage, including the fact that when he was a teenager, he may have had a child with another young Black woman back in Dublin--before his family moved to California and never returned. Now estranged, Vincent has agreed to see Cillian again at their son's wedding the following summer, but Loup introduces new complications. Soon they begin an intense affair, and somewhere between dinners made together, nights spent talking and smoking cigarettes in the moonlight, hazy evenings in nightclubs where Loup's band plays, cafés, museums, and long, starry walks by the Seine, Vincent feels herself loosening, blossoming. Filled with playlists, travel journal entries, and excerpts from Cillian's novel, Half-Blown Rose traverses Paris, train rides, liminal spaces, and the messy complexities of relationships. As Cillian does all he can to win her back and with their son's wedding quickly approaching, Vincent must decide what she wants... and who she will be"--